KEBIJAKAN HAMBATAN PERDAGANGAN ATAS PRODUK EKSPOR INDONESIA DI NEGARA MITRA DAGANG - Umar Fakhrudin (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
Free trade is an economic concept that refers to the sale or purchase of goods and services among countries without any tariff and non tariff barriers. However, because each country has a difference resources then appears a protectionism practice of domestic production and other interests from the international pressures through the enactment of trade barriers both tariff and non-tariff (in the form of quotas, specific products, and some requirements outside the trade issues) for imported products. Various form of these obstacles is one of the causes of the difficulty of improving the Indonesia‘s exports performance to other countries. Based on the calculation of Trade Restrictiveness Indices, average of non tariff barriers added 70 percent to trade barriers derived from tariffs. In 21 countries (from total 91 countries), the contribution of non-tariff barriers to trade barriers are generally greater than the barriers of tariffs and protectionism in the agricultural sector is greater than in the manufacturing sector. On average, two times greater than protection. It shows the countries with export composition depends on agricultural products will likely face market access problems more than other countries that specialize on manufacturing products.